PENGUATAN PENGELOLAAN KEUANGAN BUMDES MANUNGGAL DADI MULYO DESA KWADUNGAN GUNUNG BERDASARKAN STANDAR AKUNTANSI KEUANGAN (SAK) SEBAGAI UPAYA MENUJU DESA MANDIRI - Khotijah, Siti Afidatul; Atika, Atika (Universitas Tidar, 2024)
The aim of the Community Partnership Program (PKM) is to provide financial management training for BUMDes Manunggal Dadi Mulyo, Kwadungan Gunung Village. BUMDes Manunggal Dadi Mulyo, Kwadungan Gunung Village has been around for a long time, but it went into hiatus and has only been restarted in the last few years. The manager of BUMDes Manunggal Dadi Mulyo, Kwadungan Gunung Village, has not carried out financial management according to financial accounting standards and also does not have the expertise to prepare financial reports. This service is carried out by providing training to the manager of BUMDes Manunggal Dadi Mulyo, Kwadungan Gunung Village, so that the manager is expected to be able to prepare financial reports independently as an effort towards an independent village. The training is not only given in theoretical form, but participants also practice recording financial reports using an application that can be installed on a smartphone, making it easier for participants to record their finances.